National access to pediatric care based on insurance type for children with buckle fractures. Issue 2 (March 2019) - Marchenko, Mikhail; Iobst, Christopher A.
Abstract : Background: Previous studies have shown that there is a disparity between access to medical care for U.S. patients with Medicaid and patients with private insurance. This difference has been determined in previous studies of pediatric access to orthopaedic care, and in this study the access to pediatric care was analyzed. Methods: Five randomly selected pediatric offices from each state were called with a fictitious scenario to schedule an appointment for a child with a simple bone fracture called a buckle fracture. Once, the office was called with the child having private insurance and the second time the same office was called with the child having Medicaid. Results: Of the 250 offices that were contacted, 221/250 (88.4%) of the offices accepted private insurance, and 113/250 (45.2%) of the offices accepted Medicaid. There was a statistically significant difference between the two groups ( P <0.0001). The percentage of offices that scheduled an appointment within 7 days was 95.5% for privately insured patients, and 83.6% for patients with Medicaid. This difference was also statistically significant ( P =0.0005). Conclusions: Although earlier studies have shown that Medicaid patients are less likely to be accepted by specialty care providers, this study determined that pediatric patients will also have more difficulty in scheduling appointments with pediatricians if they are covered by Medicaid.